1982
DOI: 10.1177/000331978203301004
|View full text |Cite
|
Sign up to set email alerts
|

Gray Hair in Black Males A Possible Risk Factor in Coronary Artery Disease

Abstract: Premature gray hair has been reported to be associated with coronary artery disease (CAD) in white males. Premature gray hair also occurs in black males despite a reported lower incidence of coronary artery disease in this group. In order to determine if premature gray hair is associated with coronary artery disease in a black male population, we prospectively studied 120 patients. Forty black males with proven CAD had gray hair in 100 percent of the cases as compared to 55 percent in a control series of 80 bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…One of the earliest clinical signs which may possibly help in recognizing early onset of CAD in a young smoker is the presence of premature graying of hair. Although this sign was described as early as in 80's by Eisentein et al (5,6) and later few studies from our centre have also shown similar results (7,8), it has become a subject of intense research only very recently in the western world (9).…”
Section: Introductionsupporting
confidence: 70%
“…One of the earliest clinical signs which may possibly help in recognizing early onset of CAD in a young smoker is the presence of premature graying of hair. Although this sign was described as early as in 80's by Eisentein et al (5,6) and later few studies from our centre have also shown similar results (7,8), it has become a subject of intense research only very recently in the western world (9).…”
Section: Introductionsupporting
confidence: 70%
“…One of the earliest clinical signs which may possibly help in recognizing early onset of CAD in a young smoker is the presence of premature graying of hair. Although this sign was described as early as in 80's by Eisentein et al ( 5 , 6 ) and later few studies from our centre have also shown similar results ( 7 , 8 ), it has become a subject of intense research only very recently in the western world ( 9 ).…”
Section: Introductionsupporting
confidence: 70%
“…Our findings also supported these observations and detailed them. Afterwards, subsequent studies with various sample sizes were performed in different patient populations including CAD, myocardial infarction in black or white men or women (5)(6)(7)(8)(9)(10)(11). Several of these reports also showed association between premature hair whitening and myocardial infarction, although many are relatively outdated and have some methodological limitations, especially in determining the extent of CAD and intensity of hair whitening.…”
Section: Discussionmentioning
confidence: 99%